The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1074/jbc.m114.564013
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β Peptide-specific DARPins as a Novel Class of Potential Therapeutics for Alzheimer Disease

Abstract: Background:The amyloid-␤ peptide (A␤) is crucially involved in the onset and progression of Alzheimer disease (AD). Results: A designed ankyrin repeat protein (DARPin) was selected to bind and neutralize A␤. Conclusion: DARPins can prevent amyloid formation and associated neurotoxic effects of A␤. Significance: DARPins provide a therapeutic potential in the treatment of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
0
19
0
2
Order By: Relevance
“…This is also true for ANK proteins [51]. One of the advantages of using DARPins is that they exhibit high affinity (in as low as picomolar concentrations) and high specificity to the target protein as well as being thermodynamically stable [66,67]. The high specificity is ascribed to their rigid interface arising from three repeated β-turns in the ANK repeats (166 residues) [56].…”
Section: Designed Ankyrin Repeat Proteins: Engineered Scaffold Proteimentioning
confidence: 99%
See 1 more Smart Citation
“…This is also true for ANK proteins [51]. One of the advantages of using DARPins is that they exhibit high affinity (in as low as picomolar concentrations) and high specificity to the target protein as well as being thermodynamically stable [66,67]. The high specificity is ascribed to their rigid interface arising from three repeated β-turns in the ANK repeats (166 residues) [56].…”
Section: Designed Ankyrin Repeat Proteins: Engineered Scaffold Proteimentioning
confidence: 99%
“…Furthermore, their potential to inhibit enzymes such as proteases, kinases and membrane proteins allosterically is vital for proper regulation and function of the body. Hanenberg et al demonstrated using mouse models DARPins' therapeutic potential in the treatment of Alzheimer's, a neurodegenerative disease characterized by short-term memory loss and even dementia [66]. Amyloid-β peptide (Aβ) -a crucial molecule involved in the inception and progression of Alzheimer's -was observed to be delayed from aggregating by binding specifically to DARPins and eventually neutralized and, ergo, prevented Aβ-mediated neurotoxicity in vitro.…”
Section: Designed Ankyrin Repeat Proteins: Engineered Scaffold Proteimentioning
confidence: 99%
“…Mitochondrial membrane rupture caused by oxidative stress allows calcium to flow into the cytoplasm, activating calcium dependent proteases and increasing intracellular free radicals. Such further damage to mitochondrial function is expected to result in neuronal energy metabolism disorders and aggravation of neurological degenerative diseases (Choi et al, 2014b;Hanenberg et al, 2014). LA, a powerful antioxidant, can inhibit the generation of oxygen free radicals and thus can regulate GSH.…”
Section: Discussionmentioning
confidence: 99%
“…и обладающего стабильной структурой из Я-поворота и двух ά-спиралей. Обычно белки представлены 4-6 модулями с суммарной молекулярной массой от 14 до 21 кДа (молекулярная масса каждого 3,5 кДа) [30,31].…”
Section: применение альтернативных каркасных белков для радио-нуклиднunclassified